Analysis and Evaluation of Energy Consumption over 4G Network - Rashid, Md Mamun Ur; Tuli, Tadele Belay (Engineering International, 2017)
The mobile communication network cuts 0.5 percent of today’s global energy consumption. Among all other constrains, energy is the most critical concern to deploy any communication network. The demand of power for wireless networks increases dramatically. By applying three novel approaches, we can minimize the power consumption of 4G wireless networks such as optimal power scheduling (OPS) for base stations, packet delay scheduling (PDS) and sleep mode for variable traffic density (SMVTD). This paper presents energy consumption issues over the 4G wireless network and its associated constraints such as finding the optimal radio base stations to reduce the energy and cost for the entire system. Within same network coverage area if we optimize the number of base stations, then it will be a hallmark to minimize the energy cost. We have considered the various element concerning the 4G network and responsible parameters for energy consumption. We also studied the different mode of variable traffic density in 4G network.
Keywords: 4G; LTE; BTS; sleep mode; packet delay; traffic density